2020
DOI: 10.4102/aveh.v79i1.590
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and staging of ocular surface squamous neoplasia

Abstract: Background: Ocular surface squamous neoplasia (OSSN) is the most common ocular tumour. The diagnosis of OSSN is based on clinical suspicion and confirmed by various diagnostic modalities, of which histology is the gold standard. With the move to less invasive management options such as topical chemo- or immunotherapy, less invasive diagnostic options have come to the fore.Aim: The purpose of this article was to review the current staging and diagnostic modalities for OSSN with a focus on less invasive modaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Still, the most compelling advantage of IFN- α 2b is a better safety profile in comparison to MMC or 5-FU, both of which often cause more pain and hyperaemia after instillation 7 , 8 , 20 . Furthermore, severe corneal side effects such as limbal stem cell deficiency, scleral melt, and punctal stenosis have been associated with MMC use; equally, 5-FU may cause lid swelling and punctate epithelial erosions 20 , 21 , 22 . Clinical efficacy of the three chemotherapeutic agents appears to be equal, but prospective clinical trials have not been performed so far 7 , 8 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Still, the most compelling advantage of IFN- α 2b is a better safety profile in comparison to MMC or 5-FU, both of which often cause more pain and hyperaemia after instillation 7 , 8 , 20 . Furthermore, severe corneal side effects such as limbal stem cell deficiency, scleral melt, and punctal stenosis have been associated with MMC use; equally, 5-FU may cause lid swelling and punctate epithelial erosions 20 , 21 , 22 . Clinical efficacy of the three chemotherapeutic agents appears to be equal, but prospective clinical trials have not been performed so far 7 , 8 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…OCT has become the favoured non-invasive diagnostic modality for OSSN. 3 Studies have reported sensitivities of 94-100% with speci cities of 100%. 5,6 Our study had lower sensitivity and speci city overall, but with a 100% sensitivity for SCC.…”
Section: Discussionmentioning
confidence: 99%
“…2 The gold standard for diagnosis is a biopsy with histology. 3 In recent years there has been a move from surgical management to the use of topical chemo or immunotherapies. 4 This has spurred the adoption of noninvasive modalities for diagnosis and the monitoring of response to therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…105 Ocular surface squamous neoplasia Thickened disorganised conjunctival epithelium with mitotic figures superficial to the basal epithelium. 119 agents, such as CS, cyclosporin and tacrolimus, have been successfully used as an adjunct. 2,120 Topical steroids should be used with caution as they inhibit collagen synthesis and may increase the risk of perforation.…”
Section: Pityriasis Rubra Pilarismentioning
confidence: 99%